Nutritional Status and Short Term Outcome of Hospitalized Patients with Stroke - Chowdhury, Md Moazzem Hossain; Kabir, Sheikh Khairul; Alam, Muhammed Syedul; Kabir, AKM Humayon; Paul, Sujat; Shouaibe, Mohammad Kawser Uddin; Waez, Md Shakeel (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Nutrition and stroke is an interrelated problem now-a-days. They influence the pattern and outcome of the stroke. The purpose of this study is to see the different nutritional parameters with their interrelation with stroke and in-hospital outcome of admitted stroke patients. It is a hospital based descriptive cross sectional study conducted on purposively selected (non-probability) hospitalized patients who had been admitted into the neurology wards, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during a period of 6 months. Cases (n = 50) with CT scan of brain done were interviewed and examined and had measurements of height, weight, waist and hip circumference, waist-to-Hip Ratio (WHR) and Mid-Upper Arm Circumference (MUAC) calculated along with serum albumin level. Out of 50 patients of this study 36 (72%) were males and 14 (28%) were females; Male to female ratio was 2.6:1. It was found that 26 (52%) patients were 60 years and above, 1 (2%) in the age group of 20-30 years, 3 (6%) in the age group of 30-39 years, 4 (8%) in the age group of 40-49 years and 16 (32%) were in the age group of 50-59 years The mean hip circumference of the study people was 95 cm. WHR was calculated for each patient, the result of which shows that 33 (66%) patients had abnormal WHR while 17 (34%) patients had been found to possess normal WHR. Body Mass Index (BMI) was calculated for each patient, the result of which shows that 24 (48%) patients had abnormal BMI while 26 (52%) patients had been found to possess normal BMI. MUAC was calculated for each patient, the result of which shows that 22 (44%) patients had abnormal MUAC while 28 (56%) patients had been found to possess normal MUAC. Serum albumin level was measured for each patient, the result of which shows that 17 (34%) patients had low serum albumin (<3gm/l) while 33 (66%) patients had been found to possess normal serum albumin (>3gm/l). Regarding analysis of BMI and WHR with different types of stroke WHR was found significantly different regarding normal and abnormal records (p<0.05). Regarding BMI it was not significant (p>0.05). Among 50 patients with stroke 32 (64%) patients got either partial (44%) or clinical recovery (20%) from the disease, 12 (24%) patients showed no noticeable improvement and 6 (12%) patients expired. The results revealed that nutrition has some influence and association with stroke and in-hospital outcome of the stroke patient varies. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 61-64